Growth feature of PTFE coatings on rubber substrate by low‐energy electron beam dispersion†. (11th November 2015) - Liu, Zhubo; Zhou, Bing; Rogachev, A. V.; Yarmolenko, M. A.
Abstract : Polytetrafluoroethylene (PTFE) coatings were prepared on Si and acrylonitrile‐butadiene rubber substrates by low‐energy electron beam dispersion. The effects of substrate nature, distance of target to substrate (dts ) and coatings thickness on the surface morphology, structure, and tribological properties of the coatings were investigated. The results showed that substrate nature affects the shape and size distribution of surface conglomerations of PTFE coatings due to the interaction process of active dispersion particles with underlying polymer layer. Surface energy of PTFE coatings decreases first with the coatings thickness increases to 1.25 µm and then slowly increases with the thickness. Structure defects (pore, interstice, and so on) in the coatings increase with the thickness increases but reduce significantly with the dts increases. PTFE coating prepared at the dts of 20 cm had a higher intensity of the amorphous absorption bands. Friction experiment indicated that the destroyed area of the coatings in the friction region decreases with increases the coatings thickness but increases with the dts . The rubber modified by PTFE coatings with spherical structure possesses a higher stability in the friction process and a lower coefficient of friction. Copyright © 2015 John Wiley & Sons, Ltd.